Multiple occurrence of premature polyarticular osteoarthritis in an early medieval Bohemian cemetery (Prague, Czech Republic) - Drtikolová Kaupová, Sylva; Velemínský, Petr; Cvrček, Jan; Džupa, Valér; Kuželka, Vítězslav; Laboš, Marek; Němečková, Alena; Tomková, Kateřina; Zazvonilová, Eliška; Kacki, Sacha (International journal of paleopathology, 2020)
OBJECTIVES: To highlight conditions that may cause early-onset degenerative joint disease, and to assess the possible impact of such diseases upon everyday life. MATERIAL: Four adults aged under 50 years from a medieval skeletal collection of Prague (Czechia). METHODS: Visual, osteometric, X-ray, and histological examinations, stable isotope analysis of bone collagen. RESULTS: All four individuals showed multiple symmetrical degenerative changes, affecting the majority of joints of the postcranial skeleton. Associated dysplastic deformities were observed in all individuals, including bilateral hip dysplasia (n = 1), flattening of the femoral condyles (n = 3), and substantial deformation of the elbows (n = 3). The diet of the affected individuals differed from the contemporary population sample. CONCLUSIONS: We propose the diagnosis of a mild form of skeletal dysplasia in these four individuals, with multiple epiphyseal dysplasia or type-II collagenopathy linked to premature osteoarthritis as the most probable causes. SIGNIFICANCE: Combining the skeletal findings with information from the medical literature, this paper defines several characteristic traits which may assist with the diagnosis of skeletal dysplasia in the archaeological record. LIMITATIONS: As no genetic analysis was performed to confirm the possible kinship of the individuals, it is not possible to definitively assess whether the individuals suffered from the same hereditary condition or from different forms of skeletal dysplasia. SUGGESTIONS FOR FURTHER RESEARCH: Further studies on premature osteoarthritis in archaeological skeletal series are needed to correct the underrepresentation of these mild forms of dysplasia in past populations.
Keywords: Diet; osteoartróza; Adult; Male; hřbitovy; Hip Dislocation; lidé; lidé středního věku; Cemeteries; Humans; Middle Aged; luxace kyčle; dieta; Czech Republic; mužské pohlaví; Osteoarthritis; kosti a kostní tkáň; Bone and Bones; dospělí; Česká republika; ženské pohlaví; Female; History, Medieval; dějiny středověku